Performance of turkeys under different energy and protein levels in hot and humid condition - PANDA, N; DUTTA, G; MISHRA, S C; MISHRA, P K (The Indian Journal of Animal Sciences, 2011)
Beltsville small White turkeys (162), 12–week–old, were divided into 9 groups with 3 replications in each having 6 turkeys per replication. Nine dietary treatments, containing 3 energy levels (2500, 2700 and 2900 K.cal/kg) and 3 crude protein levels (18, 16 and 14%) in a 3×3 factorial design during growing period (12 to 24 weeks) were tried. Weekly body weight, body weight gain, feed consumption, feed efficiency and carcass characteristics and economics were calculated. No significant difference of body weight was found in the turkeys up to 16 weeks of age, but from 17 to 24 weeks the body weight gain and cumulative body weight gain of T7 (CP 18$, ME 2900 K cal/kg) and T8 (CP 16%, ME 2900 Kcal/kg) groups were significantly higher than all other groups. The cumulative feed consumption of the turkeys during the growing period receiving ME 2500 K cal/kg was the highest followed by medium energy group (ME 2700 K cal/kg). Irrespective of protein content of the feed with the increase in energy content the intake of feed decreased progressively. The best cumulative feed efficiency was noticed in the turkeys of T7 and the poorest being the T2 (CP 16%, ME 2500 K cal/kg). No significant difference among the treatments for dressed yield, eviscerated yield, neck yield, wing yield, back yield and giblet yield of the turkeys were found. But significant difference for live or preslaughter weight, breast yield, thigh yield, drumstick yield and abdominal fat yield were recorded. Lowest feed cost per kg live weight gain was obtained as Rs 43.50/ in T8 group (CP 16%, ME 2900 K cal/kg). It is concluded that the Belts Ville Small White grower turkeys at the abe of 12–24 weeks perform better at the energy level of 2900 K cal/kg of feed with the CP content of 16% in the diet in hot and humid climate.